Evaluation of Marginal Fit of CAD/CAM Ceramic Crowns and Scanning Time Using Different Intraoral Scanning Systems - Leandro Maruki Pereira; Bárbara Inácio de Melo; Alex Antônio Maciel Oliveira; Gustavo Mendonça; Luís Henrique Araújo Raposo; Marcel Santana Prudente; Flávio Domingues das Neves (Journal of Functional Biomaterials)
This study aimed to evaluate the scanning time and marginal fit of CAD/CAM crowns fabricated using different intraoral scanning systems (IOS) (O1—Omnicam 1.0, O2—Omnicam 2.0, PS—Primescan). A standardized, 3D-printed composite resin die with a full-crown tooth preparation was scanned ten times with each IOS, and the scanning time was recorded. Subsequently, lithium disilicate ceramic crowns were designed and milled. The crowns were seated in the die and scanned using micro-computed tomography to assess the marginal fit. Fifty-two measurements were performed for each crown. Data were assessed for homogeneity, and one-way analysis of variance and the Tukey HSD test were performed (α = 0.05). For the analysis of vertical fit categories, the chi-square (Fisher’s exact) test (α = 0.05) was used. The mean vertical fit values were: O1—46.7 ± 16.4 μm, O2—33.8 ± 21.4 μm (p = 0.041), and PS—12.3 ± 6.6 μm (p < 0.001). The vertical fit values were further categorized by percentage and representative specimens were scanned with electron microscopy to evaluate adaptation. The mean scanning times were: O1—37.4 ± 3.1 s; O2—34.8 ± 2.7 s; and PS—27.8 ± 1.9 s. Significant differences were observed in the scanning times and marginal fit values of the CAD/CAM ceramic crowns across the different IOS systems, with PS demonstrating the best results. Improvements in IOS hardware and software significantly influence these outcomes.